(untitled) (Research, Society and Development, 2020)
University extension, through the teaching-research-extension tripod, favors the transfer of knowledge, crossing the university walls and enhancing the effects of health education. This article aims to describe, in the form of an experience report, the extension project “Safe community: education of the population in first aid and disease prevention”, which developed theoretical-practical educational actions on topics related to first aid in urgent situations and emergency common in the daily life of the population. The actions of the project were carried out between March 2019 and February 2020 in the Basic Health Units, in the municipality of Parnaíba - PI and developed by professors and students of the medical course, members of an academic league, from the application of theoretical content for UBS users who sought health care, through pamphlets and lectures in the waiting rooms and after practical simulations to explain the correct conduct in first aid such as burns, cardiopulmonary stops, traffic accidents and poisoning by poisonous animals. The educational process promoted by extension workers allowed the population to have access to the contents, whose practical applications can reflect benefits in health situations and allowing the demystification of beliefs and cultural practices that harm the victim’s prognosis.